Analysis Factors of Bacteria in The Refill Water at Semarang District (Universitas Negeri Semarang, 2018)
Refill Drinking Water is a drinking water industry business that processes raw water into drinking water. Semarang is an industrial city in Central Java, an increase in the number of industrial companies is raised so that the development activities in various fields can directly cause microbial pollution in raw water. The purpose of this study was to analyze the effect of raw water sources, filtration processes, disinfection processes, environmental sanitation conditions and personal hygiene in the presence of bacteria in refill drinking water in Semarang district. This research was a quantitative research, with a cross sectional approach. The research sample amounted to 33 refill drinking water stations with simple random sampling technique. The instrument used was the observation sheet and the form of laboratory test results. Data collection techniques used interviews, observations and laboratory tests. Data analysis in this study used Simple Logistic Regression. The results of the study were influential on raw water source variables (p = 0.019), filtration process (p = 0.017), disinfection process (p = 0.013), environmental sanitation conditions (p = 0.017), personal hygiene of employees (p = 0.013) on existence bacteria in refill drinking water in Semarang district. The presence of E. coli bacteria in refill drinking water indicates microbial pollution in drinking water, which can result.